2017
DOI: 10.1002/acp.3318
|View full text |Cite
|
Sign up to set email alerts
|

Examining Relations between Aging, Life Story Chapters, and Well‐Being

Abstract: Socio-emotional selectivity theory holds that older age is associated with a sense of limited remaining time. We suggest that life story chapters may be involved in this experience. In this first study on the connection between socio-emotional selectivity theory and chapters, we examined whether older age is associated with fewer, temporally less distant, and less positive future chapters. We also examined relations between chapters and subjective well-being. Two samples (18-84 years) described past and future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Contrary to our first hypothesis, we did not find a PE of aging for life narrative memories, even though we studied a wide age range, but rather a reverse, negative effect. The few previous studies of the format of AMs closest to life narratives, life story AMs (Jensen et al, 2020 ; Thomsen et al, 2017 ), had found no PE either. The comparison to studies of cued and self-relevant AMs most of which found a PE suggests that the PE in AM highly depends on the method with which memories are elicited.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Contrary to our first hypothesis, we did not find a PE of aging for life narrative memories, even though we studied a wide age range, but rather a reverse, negative effect. The few previous studies of the format of AMs closest to life narratives, life story AMs (Jensen et al, 2020 ; Thomsen et al, 2017 ), had found no PE either. The comparison to studies of cued and self-relevant AMs most of which found a PE suggests that the PE in AM highly depends on the method with which memories are elicited.…”
Section: Discussionmentioning
confidence: 89%
“…Second, we externally coded the valence of memories but did not ask participants to evaluate the affective tone of their life narrative memories themselves. Although previous studies of life story AMs that were self-rated on affective tone did not find a PE either (Jensen et al, 2020 ; Thomsen et al, 2017 ), external and self-ratings of affectivity should be compared in the same study. Third, an experimental approach could compare the influence of varying constraints in different elicitation methods on the selection and the affective tone of AMs.…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Seniors also depend more on their intimates (e.g., children and partners), indicating the importance of their attachments (Antonucci et al, 2004). According to the socio-emotional selectivity theory, seniors may perceive that their life years are is limited as they become older, and therefore, they are more likely to seek deep emotional meaning in the present, rather than make new friends (Carstensen et al, 2003;Löckenhoff and Carstensen, 2004;Kirkegaard Thomsen et al, 2017). In Asian cultures, people have high regard for families and intimate relations, and attachment plays a significant role in the mental health of older Chinese adults.…”
Section: The Effect Of Attachment On Depressionmentioning
confidence: 99%
“…This concept of successful aging, based on objective indicators, has recently been expanded to include positive psychology indicators ( Ardelt, 2016 ). One’s subjective attitude toward the physical and social changes that occur in old age play a crucial role in predicting well-being in this stage of life ( Thomsen et al, 2017 ). Thus, aging is a multidimensional process.…”
Section: Introductionmentioning
confidence: 99%